Knowledge Sharing in Research Collaborations Understanding the Drivers and Barriers - Niedergassel, Benjamin (Gabler, 2011)
In the knowledge-driven economy, individuals and organizations need to look beyond their own boundaries to complement existing resources. Especially in research-intensive fields, effective and efficient knowledge sharing with collaboration partners has become the key to success. Based on a large-scale survey, Benjamin Niedergassel identifies several factors enhancing or inhibiting knowledge sharing in research collaborations. He uses these factors to derive practical implications for academia, industry and research policy.